IMPLEMENTASI PEMBELAJARAN DARING PADA MASA COVID-19 - Sitti Marlina (Cross-border, 2021)
This research was conducted to determine the implementation of online learning at SMK Yaspib Bontolempangan. This study uses a quantitative method with a case study approach. Data collection is done by interview. The data analysis technique used is descriptive qualitative analysis. Based on research data, it was found that learning during the Covid-19 period was carried out online. Online learning is carried out using the whatsapp application. Online learning is carried out on good cooperation between teachers, students, and parents during online learning and assignments given by the teacher. The process of teaching and learning activities does not run effectively and efficiently due to limitations on the internet network.